Analysis of The Suitability of Eleventh Grade Physics Textbooks with the Independent Curriculum - Erlina Puspita Wahyuningtyas; Ellianawati Ellianawati (UPEJ Unnes Physics Education Journal, 2023)
The emergence of the COVID-19 (Coronavirus Disease) pandemic in Indonesia at the end of 2019 became a turning point in all aspects of life, one of which was education which implemented a distance learning policy. This policy causes learning loss (loss of interest in learning) for some students. Efforts made by the government to overcome the problem of learning losses are by changing the curriculum. Learning resources in the form of subject text books used in schools are one of the learning media that has been affected by curriculum changes. The advantages and disadvantages of subject textbooks can be identified by conducting an analysis. This research was conducted with the aim of knowing the suitability of a physics textbook by authors Mike Crundell and Geoff Goodwin entitled "Physics for Class XI SMA" with the five aspects of the Independent Curriculum by using the documentation or text analysis method, in which the researcher analyzed, described, explained, described, write, and report the state of objects or data obtained from data sources. Based on the results of the analysis, it is known that the suitability of the book with the Graduate Competency Standards aspect averages 92.85% with the very good category, the percentage results of suitability with the Learning Outcomes aspect average 74.28% with the sufficient category, then the percentage of suitability results with the Average Objective aspect the learning average is 72.14% in the sufficient category, the results of the percentage of suitability with the Material Coverage aspect are on average 90% in the very good category, and the percentage of results according to the Depth of Material aspect is an average of 91.42 included in the very good category.